Postnatal Factors Associated With The Risk Of Stunting In Toddlers - Risa Nurhayati; Dewi Indriani; Rahayu Budi Utami (Universitas STRADA Indonesia, 2020)
The design of this study uses observational analytical research with case control design. A sample of 450 toddlers was selected using fixed disease sampling which included a case group of 150 toddlers with stunting and a control group of 300 normal toddlers who were not in stunting, wasting and overweight conditions. The data collection tool uses questionnaires and data processing using double logistic regression analysis. Stunting is influenced by the length of the birth body (OR=3.14; CI 95%=2.42 to 3.86; p=<0.0001), breastfeeding (OR=2.31; CI 95%=1.69 to 2.93; p=<0.0001) and history of infectious diseases (OR=2.26; CI 95%=1.61 to 2.91; p=<0.0001). Birth weight has no effect on stunting events (OR=1; CI 95%=0.32 to 1.68; p=0.004). The incidence of stunting increases with less birth length, unsy exclusive breastfeeding and the absence of a history of infectious diseases in toddlers